The Effect of Two Different Root Canal Sealers on Post Obturation Pain - Nabiya Shahroz, Sumayya Surti, Irha Hussain Zaidi, Mohammad Aun Ali Mehdi, Shahroz Sajjad, Zain Noor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to evaluate the effectiveness of various root canal sealers in reducing postoperative pain and the need for analgesics. Methods: The asymptomatic necrosis and apical periodontitis of 60 single-rooted teeth were studied by randomly assigning them to 2experimental groups (n=30) according to the root canal sealer: AH Plus and MTA Fillapex. Two appointments were needed to complete the endodontic treatment, and calcium hydroxide was employed as the intracanal dressing. The patients were asked to assess the severity of their discomfort as no pain, slight and moderate pain. After 24 hours, 48 hours, and 7 days, patients rated their discomfort on a scale from 1 to 4. The use of pain relievers was also documented. Postoperative pain and the requirement for analgesia were compared using the t-test. Results: The Mean±S.D of the participants age in AH plus and MTA Fillapex group was 39.1±9.4 and 43±9.2 years. Overall, 62% were female and 38% were males were included in the present research. Overall, 37% of the cases (22 patients) had postoperative discomfort after 24 hours, with the number decreasing to 18% (11 patients) after 48 hours. After 7 days, no one in either of the groups had any discomfort. There were no statistically significant differences between groups in the occurrence or severity of postoperative pain or in the use of analgesics at any of the assessment points. Conclusion: Similar rates of postoperative discomfort and the requirement for analgesics were seen with the use of either AH Plus or MTA Fillapex for root canal filling. Keywords: Pain, Postoperative; Root Canal Obturation; Clinical Study